Review paper of Vehicle control system using CAN protocol - Dr. Miss. J. D. Dhande; Snehal V. Sakle; Prof. Mr. R. D. Kadam (Research Parks Publishing LLC, 2021)
Nowadays economical automobiles are developed by more of electro mechanical parts with analog interface for efficient & cost-effective operation. Generally, a vehicle is built with an analog driver-vehicle interface for indicating various vehicle statuses like speed, fuel level, engine temperature etc. This paper presents a design & development of cost-effective solution for digital driving interface with a semi-autonomous vehicle improving the driver-vehicle interaction with increase in safety. Our designed system uses sensors to digital format and visualize them to the vehicle driver through a LCD display. The communication module used here is an embedded network bus CAN, which has efficient data transfer.